Post-Harvest Handling of Coffee through Coating Application with Zero-waste Concept to Support Green Economy in Wanagiri Village, Sukasada District, Bali: Post-Harvest Handling of Coffee through Coating Application in Wanagiri Village, Sukasada District, Bali - Suriati, Luh; Kaca, I Nyoman; Wirajaya, Anak Agung Nguran Mayun; Rabani RS, I Gusti Agung Yogi; Padmarini, Ni Made Andira; Putri, Putu Ananda Icaka; Dewi, Ni Made Putri Pradnya Paramita; Darmawan, Kadek Dinda Rahayu; Patni, Gusti Ayu Yunda Darma (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
The objective of this activity is to enhance the knowledge of the community in Wanagiri Village on more effective and efficient coffee farming techniques, to improve the productivity and quality of life for coffee farmers in the area. The training will focus on developing skills in coffee cultivation, post-harvest processing, and product diversification. The specific type of coffee being highlighted is robusta Wanagiri coffee, which has gained international popularity due to its unique aroma and flavor. The planned activities will include face-to-face training, counseling, and hands-on practice, where experts will provide guidance and support to help the partners understand and apply the technology provided. The ultimate goal is to enable the partners to improve their coffee production and develop diverse coffee products, such as ground coffee, green bean coffee, and instant specialty coffee, to reach a wider market. This activity is scheduled to take place in Wanagiri Village, Sukasada District, Buleleng Regency on August 5th, 2024. After the training and exercise, it was found that the participants understood the material presented by the resource person and were very interested in applying a coating to their coffee to reduce farmer losses and to utilize or process coffee husk waste into animal feed to be fed directly to their livestock or to become organic fertilizer. Good post-harvest handling, including the application of coating technology, is very important in maintaining coffee quality, particularly in preserving aroma and flavor during storage and transport. In addition, the application of zero-waste technology in coffee processing has the potential to reduce waste and increase the value of coffee by-products